HOW THE ELITE ARBITRATES (LAW AND POLITICS) - Raharjo, Agus (Jurnal Dinamika Hukum, 2015)
There were two notable events in the history of law enforcement in Indonesia. First, regarding with the old story that was often written in this section, namely the eradication of corruption; and the second was an event that seemed became institutionalized in the form of split within the party after the congress. The first issue certainly could not be separated from the previous events, in which the resistance of National Police (Polri) against the establishment of Police Commissioner General Budi Gunawan done by other channels, namely through the pre-trial. Many were hoping the court did not pass the pre-trial plea for establishing the status of a suspect on the Police Commissioner General Budi Gunawan because of the criminal procedural law, pre-trial plea for setting the suspect did not exist or was not regulated. After all the efforts made by Police Commissioner General Budi Gunawan was not in accordance with the spirit of anti-corruption that were inflamed and became one of the government work program Joko Widodo - Jusuf Kalla.......